The Mayo Clinic diet : reshape your life with science-based habits - Hensrud, Donald D. (Mayo Clinic Press, 2023)
"This revised edition of the #1 New York Times bestselling book offers a simple, time-tested, no-nonsense way to lose weight and keep it off. The Mayo Clinic Diet is an approach that draws on years of research from thousands of individuals seeking to lose weight. It's a plan for a sustainable lifestyle, not just a diet...New to this edition, you'll find recipes and meal plans to fit a variety of eating styles including keto, the Mediterranean diet, vegetarian and higher protein. Step by step, The Mayo Clinic Diet teaches the habits, tips and tricks that will help you lose weight and keep it off for good"--